1988
DOI: 10.1056/nejm198809293191304
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a High-Carbohydrate Diet with a High-Monounsaturated-Fat Diet in Patients with Non-Insulin-Dependent Diabetes Mellitus

Abstract: We compared a high-carbohydrate diet with a high-fat diet (specifically, a diet high in monounsaturated fatty acids) for effects on glycemic control and plasma lipoproteins in 10 patients with non-insulin-dependent diabetes mellitus (NIDDM) receiving insulin therapy. The patients were randomly assigned to receive first one diet and then the other, each for 28 days, in a metabolic ward. In the high-carbohydrate diet, 25 percent of the energy was in the form of fat and 60 percent in the form of carbohydrates (47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
164
5
3

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(192 citation statements)
references
References 38 publications
20
164
5
3
Order By: Relevance
“…The small increments in HDL cholesterol on a highmonounsaturated fat diet have been reported by some investigators (Garg et al, 1988;Coulston et al, 1989) although we did not observe a statistically signi®cant reduction in triacylglycerol concentration as they also described. However, a number of other studies, most of which were conducted in outpatients, have failed to show any changes in plasma lipids (Bonanome et al, 1991;Rasmussen et al, 1993;Walker et al, 1995).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The small increments in HDL cholesterol on a highmonounsaturated fat diet have been reported by some investigators (Garg et al, 1988;Coulston et al, 1989) although we did not observe a statistically signi®cant reduction in triacylglycerol concentration as they also described. However, a number of other studies, most of which were conducted in outpatients, have failed to show any changes in plasma lipids (Bonanome et al, 1991;Rasmussen et al, 1993;Walker et al, 1995).…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, studies done under metabolic ward conditions with insulin using type 2 patients (Garg et al, 1988), and studies using outpatients (Garg et al 1994, Campbell et al, 1994Walker et al, 1995) have found signi®cant reductions in concentrations of plasma glucose, insulin, triacylglycerol and VLDL cholesterol, and elevated HDL cholesterol concentrations after four weeks on a high-mono diet. A recent meta-analysis (Garg et al, 1998) has con®rmed that high monounsaturated fat diets reduce plasma triacylglycerol by 19% and modestly increase HDL cholesterol compared with high CHO diets.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In patients with established diabetes, high-fat diets increased fasting and postprandial glucose and insulin concentrations. However, it was reported by Garg et al (1988) that the high-MUFA diets resulted in improvements in glycemia. In the present study, no significant differences were observed in fasting glucose concentration in the group of hazelnut-enriched diet compared to others.…”
Section: Effects Of Hazelnut-enriched Diet On Plasma Lipid Profiles Smentioning
confidence: 99%
“…Omega 3 PUFA have wide-ranging cardiovascular protective capacities including lowering of plasma VLDL cholesterol and triacylglycerol (TG) concentrations (Connor & Connor, 1997). Consequently, it is entirely possible to consume relatively high-fat diets that do not necessarily produce a plasma lipid profile that promotes CVD (Garg et al, 1988;Nelson et al, 1995) given sufficient MUFA, PUFA (Gardner & Kraemer, 1995;Mensink & Katan, 1992) and an appropriate o-6=o-3 PUFA ratio (Connor & Connor, 1997) relative to the hypercholesterolemic fatty acids.…”
Section: Diet and Cardiovascular Disease In Hunter-gatherersmentioning
confidence: 99%